The Case of the Disappearing Spindle Burst - Alexandre Tiriac; Mark S. Blumberg (Neural Plasticity)
Sleep spindles are brief cortical oscillations at 10–15 Hz that occur predominantly during non-REM (quiet) sleep in adult mammals and are thought to contribute to learning and memory. Spindle bursts are phenomenologically similar to sleep spindles, but they occur predominantly in early infancy and are triggered by peripheral sensory activity (e.g., by retinal waves); accordingly, spindle bursts are thought to organize neural networks in the developing brain and establish functional links with the sensory periphery. Whereas the spontaneous retinal waves that trigger spindle bursts in visual cortex are a transient feature of early development, the myoclonic twitches that drive spindle bursts in sensorimotor cortex persist into adulthood. Moreover, twitches—and their associated spindle bursts—occur exclusively during REM (active) sleep. Curiously, despite the persistence of twitching into adulthood, twitch-related spindle bursts have not been reported in adult sensorimotor cortex. This raises the question of whether such spindle burst activity does not occur in adulthood or, alternatively, occurs but has yet to be discovered. If twitch-related spindle bursts do occur in adults, they could contribute to the calibration, maintenance, and repair of sensorimotor systems.